Role of imaging in the diagnosis and management of mixed epithelial and stromal tumors of the kidney: Case series and comprehensive review - Kasha Chen, BS; Jasmine Zhao, MD; Ali Sasani, BS, MS; Ryan Sabour, BS; Hannah Cho, BS; Riya Bansal, BS; Chang Shu, BSEE, MSEE, MSCS; Ryan O'Connell, MD; Roozbeh Houshyar, MD (Radiology Case Reports)
Mixed epithelial and stromal tumor (MEST) of the kidney is a rare benign neoplasm composed of both stromal and epithelial components. MEST is mainly seen in adults with a strong predilection for perimenopausal women with history of hormone replacement therapy. While MEST is generally benign, there are reported cases of malignant transformation and adverse clinical outcomes. This case series will present 7 cases of this rare renal neoplasm with emphasis on radiological imaging as an important tool in the guidance of clinical management. Considering the rarity of this tumor and its variable presentation, understanding the radiological features on multiple modalities can guide appropriate clinical and surgical management of MEST patients.